2023
DOI: 10.1093/imanum/drad034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of a finite volume scheme for charge transport in perovskite solar cells

Abstract: In this paper, we consider a drift-diffusion charge transport model for perovskite solar cells, where electrons and holes may diffuse linearly (Boltzmann approximation) or nonlinearly (e.g., due to Fermi–Dirac statistics). To incorporate volume exclusion effects, we rely on the Fermi–Dirac integral of order $-1$ when modeling moving anionic vacancies within the perovskite layer, which is sandwiched between electron and hole transport layers. After nondimensionalization, we first prove a continuous entropy-diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In one of the papers supporting the development of ChargeTransport.jl [22], Abdel et al [8] proved the convergence of their finite volume scheme for non-Boltzmann statistics and demonstrated that their code functions in accordance with their theoretical work. A strength of finite volume methods, such as those developed by Abdel et al [8] is that they are designed to ensure that physical quantities are conserved and that fluxes are estimated accurately. While ChargeTransport.jl was developed with the aim of modelling perovskite solar cells, one possibility for further work would be to explore whether ChargeTransport.jl could be modified to model OLEDs.…”
Section: Numerical Methods For Drift-diffusion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the papers supporting the development of ChargeTransport.jl [22], Abdel et al [8] proved the convergence of their finite volume scheme for non-Boltzmann statistics and demonstrated that their code functions in accordance with their theoretical work. A strength of finite volume methods, such as those developed by Abdel et al [8] is that they are designed to ensure that physical quantities are conserved and that fluxes are estimated accurately. While ChargeTransport.jl was developed with the aim of modelling perovskite solar cells, one possibility for further work would be to explore whether ChargeTransport.jl could be modified to model OLEDs.…”
Section: Numerical Methods For Drift-diffusion Modelsmentioning
confidence: 99%
“…As a result, the literature that deals with modelling and numerical solution of the latter is directly relevant to modelling and simulating OLEDs. Examples of such works include [5,6,7,8,9,10].…”
Section: Project Goalmentioning
confidence: 99%